Intra-urban Differences in Maternal Health Care Service Utilization in Nepal: Results from 2016 Nepal DHS - Dulal, Komal Prasad (Scholars’ Journal, 2023)
After restructure of local bodies in Nepal, some rural settings before 2015 fall under urban set tings. It is advantageous to understand the situation of maternal health care utilization among poor and non-poor in the new urban structure. Officially, one-fifth of the total population is poor in the country. The objective of this study is to explore the differentials in utilization of all the care designed during the course of reproduction from the notice of pregnancy to postnatal care within two days of delivery among urban poor and non-poor in Nepal. Differentials and roles in utilization of all care, utilization of full maternal health care service for the healthy pregnancy and childbirth are explored among the two economic groups living in urban setting of Nepal. This study has utilized Nepal demographic and health survey 2016 women’s data file. The data used for the analysis came from the 2016 Nepal Demographic and Health Survey (NDHS). This survey is nationally representative population-based household surveys that collected information on fertility, family planning, maternal and child health etc among other data. Details about the survey designs and sampling procedures of this survey are explained in publicly available final report. Using wealth index used as a proxy for household economic status, the lowest wealth quintile is taken as poor and the remaining as non-poor. Result shows that nearly 10 percentage point differences have been observed in utilizing recommended months of antenatal care visits as well as full antenatal care among poor and non-poor. Such differences remained three times more extensive in receiving de livery care from skilled birth attendants and the postnatal care within two days of delivery among those groups. Even, urban poor women are less likely to receive all components of maternal health care. Results of logistic regression confirm the lower chance of receiving full maternal health care by urban poor. The study concludes that urban setting, as local body of Nepal, needs to address the urban poor especially in utilization of maternal health care in protecting and saving health of mother and the newborn.